Pendidikan Karakter Di Era Society 5.0 Pada Lembaga Pendidikan - Ardina Maharani; Mukh Nursikin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This article aims to analyze character education in the era of society 5.0 in educational institutions. Character education is very important to instill in students in the current era. The era of society 5.0 is a concept that emphasizes the integration between technology and humans in achieving social and sustainable welfare. This research is a library research, where data is obtained through references to books, articles, and scientific papers related to the topic of discussion. The results showed that the development and implementation of character education in the era of society 5.0 in educational institutions brought significant changes to education and teachers must be ready to face changes by mastering technology and developing skills. It is also expected to form a young generation that has morals and Pancasila values which include honesty, creativity, discipline, communication skills, innovation, self-confidence, tolerance, and the ability to interact socially and communicate well in the school, home, and community environment.